Characteristics of Soils in the Marginal Uplands of Inopacan, Leyte - Asio, Victor B.; Lina, Suzette B.; Maranguit, Deejay S.; Bolledo, Ariel B.; Doguiles, Rizza Josefina T.; Quiñones, Cecille Marie O.; Sabijon, Jessie R.; Demain, Kier Lambert B. (Annals of Tropical Research, 2014)
Improving the productivity of marginal lands greatly depends on good understanding of the characteristics of the soils. Published data on the nature and characteristics of soils in marginal uplands are still limited. This study was conducted to determine the morphological and physico- chemical characteristics of soils in the marginal upland of Inopacan, Leyte. Five representative soil profiles located in different physiographic positions were examined and sampled. Results showed that the soils were derived from volcanic materials particularly andesite and basalt rocks. Well-developed soils were found on the summit position with the horizon sequence of Ap-Bt-BC while poorly developed soils occurred on the lower slope positions having Ap-AB-Bw-BC horizon sequence. Soils were found to be highly acidic with soil pH close to 5.0. Soil organic matter, total nitrogen and available P were low and decrease with soil depth. Exchangeable bases (Ca, Mg, K and Na) were high in most soil profiles. The results indicate that N and P fertilization as well as organic matter addition are crucial to increasing the productivity of the marginal upland soils. The marginal nature of the soils is the result of decades of unsustainable cultivation practices.